Dualisme Kedudukan Hak Guna Usaha: Perspektif Keterbukaan Informasi Publik dan Kontrak Bisnis - Pangesti, Shinta; Rumokoy, Prisca Octavia; Fahzari, Nonita Sabillah; Wirantaya, I Dewa; Hariyanti, Selin Dinda (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The Dualism of the Legal Status of Land Cultivation Rights: The Principle of Public Information Disclosure and Business Contracts. This study aims to analyze the Supreme Court’s decision in the Judicial Review (PK) ruling Number 61 PK/TUN/KI/2020 concerning the dispute over information on Land Cultivation Rights (Hak Guna Usaha/HGU) between Forest Watch Indonesia and the Information and Documentation Management Officer (PPID) of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN). The main focus of this research is to examine HGU from the perspectives of agrarian law and contract law. The method used in this study is normative juridical with a qualitative analytical approach. The statute approach and case approach are employed to examine the Supreme Court decision and the legal norms that form the basis of law in Indonesia. A dualism arises between business actors and the public: business actors view HGU as private, while the public perceives it as public. The results of the study indicate that Forest Watch Indonesia was not at fault in requesting information from the Ministry of ATR/BPN, and the Ministry itself cannot be held entirely at fault either. Reconstruction is therefore necessary to prevent conflict dualism.